MUKMIN MODEREN - Hartono Hartono (Universitas Muhammadiyah Tangerang, 2019)
Times have always changed from the classical, mid and modern. In this change, for the muttaqi mukmin, always face it as sunnatullah. A true modern mukmin can pass the challenge of thr time which cannot be thispelled. It certainly answers secularism which argue that religion is parasite in the development of the modern world.The existence of modern mukmin spread the world civilization such as in Europe and America, growing with certainly , from the increasing number of minorities and even the churches which left behind by their community and changed into mosques.Thus, Islam answers the challenges of changing times, from time to time , be coming a guide and role model for its followers and as rahmatan li al’alamin.